Philosophy of Globalization - Roldán, Concha; Brauer, Oscar Daniel (De Gruyter, 2018)
The aim of the publication is both to provide the debates on globalization with a genuine philosophical perspective by working out its normative dimensions, and to scientifically ground the ethical-philosophical discourse on global responsibility. Other topics addressed are the altering consciousness of space and time, and globalization as a discourse, as an ideology and as a symbolic form.